2014
DOI: 10.1007/s00705-014-2068-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the full-length VP2 protein of canine parvoviruses circulating in Hungary

Abstract: In recent years, the number of cases of disease caused by canine parvovirus 2 (CPV-2) in vaccinated dogs has increased. The aim of the present study was to identify CPV-2 strains present in Hungary. Forty-two out of 50 faecal specimens examined were positive, and 25 VP2 sequences were determined and analysed. Based on the current classification, the Hungarian viruses belong to New CPV-2a type, except two viruses that are recombinants of vaccine viruses and CPV-2a strains. The Tyr324Ile alteration was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 11 publications
2
25
1
2
Order By: Relevance
“…Similar codon changes at amino acid positions 324 were also reported in the CPVs isolated in different countries [28,41,[44][45][46]. Horiuchi et al [47] revealed that the residue 324 was prone to strong positive selection in all carnivorous CPV isolates.…”
Section: Discussionsupporting
confidence: 61%
“…Similar codon changes at amino acid positions 324 were also reported in the CPVs isolated in different countries [28,41,[44][45][46]. Horiuchi et al [47] revealed that the residue 324 was prone to strong positive selection in all carnivorous CPV isolates.…”
Section: Discussionsupporting
confidence: 61%
“…NS1 and VP2 sequences showed 100% nucleotide identities with Asian strains CPV/CN/LN1/2014 (China, 2014) for NS1 sequence and BJ14‐9 and BJ14‐8 (China, 2014) for VP2 sequence. Sequence analysis revealed the presence of aa changes never observed in European CPV strains (NS1: Ile60Val, Tyr544Phe, Glu545Val, Leu630Pro; VP2: Ala5Gly, Phe267Tyr, Tyr324Ile, Gln370Arg) with exception for change Tyr324Ile, which has been described in CPV‐2a isolates in Hungary (Cságola et al., ) (Table ). Phylogenetic analysis indicated that strain CPV_IZSSI_2743_17 is more related to Asian than to European CPV strains, clustering in a separate clade (Figure ).…”
Section: Resultsmentioning
confidence: 82%
“…Among these, a change at residue 324, first reported in 2006 (Zhou, Zeng, Zhang, & Li, ), may represent a common change in CPV strains circulating in the Asian continent (Geng et al., ). Recently, change Thr324Ile has been observed in European CPV‐2a strains (Cságola, Varga, Lőrincz, & Tuboly, ). The aim of this work was to report the detection and genetic characterization of a CPV strain from a dog imported from Thailand to Italy.…”
Section: Introductionmentioning
confidence: 98%
“…These data provide new evidence of the role of local genetic diversity and migration events during CPV evolution and, emphasize the dynamic changes in CPV variants and highlight the importance of ongoing surveillance programs to provide a better understanding of the virus epidemiology (P erez et al, 2012;Maya et al, 2013). However, this variability did not happen within certain countries, like Hungary (Demeter et al, 2010;Decaro et al, 2013;Cs agola et al, 2014), Japan (Ohshima et al, 2008;Soma et al, 2013) and China (Zhang et al, 2010;Yi et al, 2014), where different studies during several years showed the presence of the same predominant variant type. Based on these data, the three different antigenic variants of parvovirus, 2a, 2b and 2c, are currently circulating worldwide, being however difficult to state which is predominant.…”
Section: The Temporal and Geographic Variability And The Relative Frementioning
confidence: 80%